Liquid-induced heat treatment strategy for eliminating anisotropy of IN718 fabricated by laser powder bed fusion - Zhuoyu Li; Xiaogang Hu; Fan Zhou; Zhifang Shi; Zhiwei Lyu; Zhen Xu; Yu Li; Xin Zhao; Hongxing Lu; Qiang Zhu (Additive Manufacturing Letters)
The laser-based additive manufacturing process often results in highly textured columnar grain structures along the build direction, leading to undesirable anisotropic mechanical properties in most industrial applications. Tailored heat treatments are currently the predominant approach to address anisotropy issues. However, the lack of driving force for recrystallization during the post-heat treatment within laser powder bed fusion (LPBF) makes this method inapplicable to the process. Here, we develop a novel liquid-induced heat treatment (LIHT) post-processing. The intergranular liquid film is introduced to facilitate the columnar-to-equiaxed transition of grains in IN718 alloy fabricated by LPBF. Microstructures and mechanical properties parallel and perpendicular to the build direction have been analyzed. The degree of anisotropy in ultimate strength was reduced from 21.1% to 3.5%. The anisotropy in creep performance also decreased from 52.1% to 11.3%. LIHT is anticipated to be a typical process for eliminating the anisotropy in the mechanical properties of metallic components.